Reserve Capacity and the Kinked Demand Curve - Streeten, P. (Review of Economic Studies, 1950)
Journal Article Reserve Capacity and the Kinked Demand Curve Get access P. Streeten P. Streeten Oxford Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 18, Issue 2, 1950, Pages 103–113, https://doi.org/10.2307/2295798 Published: 01 April 1950